Association Between Perceived Access to Healthcare and the Perception of Illness Among Peruvian Adults with Chronic Diseases During COVID-19 Pandemic - Janett V. Chávez Sosa MSHCM; Haydee N. Guerra Pariona BSN; Salomón Huancahuire-Vega PhD (SAGE Publishing, 2022)
The COVID-19 pandemic has greatly affected the provision of care for patients with chronic diseases. Due to social restrictions and reductions in contact with health services, the negative perception of chronic disease is expected to have increased. The aim of this study was to determine the association between perceived access to healthcare and the perception of illness among Peruvian population with chronic disease. It was a cross-sectional analytical study, with a sample of 987 inhabitants to whom the questionnaires "Coverage of health services" and "The Brief Illness Perception Questionnaire" (BIPQ) were applied. Having health insurance (PRa = 0.683; 95% CI = 0.613-0.761) acts as a protective factor for a positive illness perception of chronic disease, however, a waiting time greater than 3 months to obtain a medical appointment (PRa = 1.417; 95% CI = 1.319-1.522) and poor access to health services (PRa = 1.435; 95% CI = 1.226-1.681) resulted in the probability of a negative illness perception of chronic disease. Thus, there is an association between perceived poor access to healthcare and the negative illness perception of chronic disease in Peruvian population during pandemic COVID-19.